Perceptions and preparedness of veterinarians to combat brucellosis through Brucellosis Control Programme in India - Shome, R.; Nagalingam, M.; Priya, R.; Sahay, S.; Kalleshamurthy, T.; Sharma, A.; Bambal, R.G.; Rahman, Habibur; Shome, B.R. (Veterinary World, 2020)
Background and Aim: Brucellosis caused by bacteria belongs to the genus Brucella is an important zoonosis and constitutes a serious public health hazard worldwide including India. The present study aimed to estimate the knowledge of veterinarians on brucellosis, its public health threat, diagnosis, and vaccination. Materials and Methods: This cross-sectional study was conducted during 2013-2015 and 453 veterinarians representing 11 states/Union Territories (UT) of India (Assam, Tripura, Meghalaya, Goa, Karnataka, Madhya Pradesh, Uttar Pradesh, Delhi, Jammu and Kashmir, Tamil Nadu, and Punjab) were interviewed using self-administered questionnaire. Results: Out of 453 veterinarians, 71.74% stated handling of the animals on day-to-day basis and 28.25% were engaged in administration activities. The veterinarians ranked foot-and-mouth disease and brucellosis at the first and fourth ranks among the list of ten economic impacted diseases in the country. A significant association was observed between laboratory confirmation with those who handled brucellosis-suspected cases (p=0.000). Similarly, significant association was noted for the availability of vials/slides (p=0.114), vacutainers (p=0.008), icebox (p=0.103), and refrigerator (p=0.106) for those who preferred laboratory diagnosis. Only 20% of the veterinarians recommended vaccination against bovine brucellosis, and 17% obtained laboratory confirmation for the brucellosis-suspected cases. Conclusion: The study highlighted the need for awareness programs, laboratory facilities, veterinary doctors, and protective measures for the veterinarians for combating brucellosis through the control program in the country.